Children's Sport Participation in Canada: Is it a Level Playing Field? - Trussell, Dawn; McTeer, William (International Journal of Canadian Studies / Revue internationale d’études canadiennes, 2007)
In this article a study of children's sport participation in Canada is presented, examining both children's participation in organized sport (with a coach or instructor) and informal sport (without a coach or instructor). This was done using a national sample survey. The results indicate that, for participation in organized sport, household income was the strongest predictor variable, followed by parent's education, gender, regional differences, and age of the child. In informal sport, gender was the strongest predictor variable, followed by regional differences, household income, age of the child, and parent's education. The findings are discussed in terms of the implications these factors may have on the development and reproduction of social division between children who are able to access sporting activities and those who cannot.